Writing Portfolio on Students’ Writing English Skill - Asri, Annisa Kurnia; Musdalifah, Musdalifah; Hidayatullah, M. Hilmy; Virgiyanti, Diska Fatima (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2023)
This research aimed to know the students’ writing a portfolio before and after being taught and to determine whether using a portfolio significantly affected their writing English skills. The research is a pre-experimental study. The population is the students of the ELT department, and the sample is 27 students who took a writing class. The instrument of this study is a writing rubric. The scores were analyzed using a t-test. The finding shows that the t-test score is 4.540, meaning the t-score is ≥ 1.729 (4.540 < -1.729). Therefore, it can be concluded that the null hypothesis is rejected, and the alternative hypothesis is accepted. It can be shown that a writing portfolio can help learners increase their writing English skills.